Pengembangan Ensiklopedia Plantae pada Mata Pelajaran Biologi SMA Berbasis Potensi Lokal Kabupaten Musi Banyuasin - Maharani Wulandari; Suratno Suratno; Sofyan Sofyan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research has a background of the gap between the need for learning resources and the availability of additional learning resources in schools. Where interesting learning resources are one way to help students achieve an understanding of the material. Plantae materials have quite a lot of material content and make students bored if they only learn using printed books and lead to lower interest and learning outcomes compared to other materials. The purpose of this study was to describe the planning, procedures for developing the encyclopedia plantae based on the local potential of the Musi Banyuasin district and the perceptions of teachers and students towards the developed encyclopedia product. This research includes the type of research and development or R&D that will produce a product. This encyclopedia research uses the ADDIE model where there are several processes, namely Analysis, Design, Development, Implementation and Evaluation. This encyclopedia is based on validation by material experts and learning media design experts with a "very valid" validity result. The subjects of this study were students in class X SMA Negeri 1 Bayung Lencir/ UPT SMAN 6 Musi Banyuasin and Biology teachers at SMA Negeri 1 Bayung Lencir/ UPT SMAN 6 Musi Banyuasin. Based on the results of the validation and trials as well as the responses given, it can be concluded that the Encyclopedia of Plantae Based on Local Potential in Musi Banyuasin Regency is feasible to use